2020
DOI: 10.5114/kitp.2020.97264
|View full text |Cite
|
Sign up to set email alerts
|

Stapler versus polyamide sutures for skin closure for sternal wounds in coronary artery bypass graft surgery – our experience

Abstract: Introduction: Patients undergoing coronary artery bypass graft surgery constitute a large population of patients with anatomically similar incisions created under similar circumstances. Aim: Our study aimed at analysing and comparing rates of surgical site infections (SSIs) at the sternotomy sites based on the material used for skin closure of the sternal wound with special emphasis on presence of risk factors such as diabetes (glycated haemoglobin (HbA 1c) > 9) and obesity (body mass index (BMI) > 30 kg/m 2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Twenty‐three thousand seven hundred and forty five participants with CS were enrolled in the chosen studies; 8730 of them used TV, while 15 015 served as controls. From a total of 1054 applicable studies that were appraised, 10 papers between 1989 and 2022 that met the inclusion criteria and were encompassed in the meta‐analysis were selected 7,14‐22 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐three thousand seven hundred and forty five participants with CS were enrolled in the chosen studies; 8730 of them used TV, while 15 015 served as controls. From a total of 1054 applicable studies that were appraised, 10 papers between 1989 and 2022 that met the inclusion criteria and were encompassed in the meta‐analysis were selected 7,14‐22 …”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of deep SWIs post CS the use of TV compared with control criteria and were encompassed in the meta-analysis were selected. 7,[14][15][16][17][18][19][20][21][22] The TV had significantly lower SWIs post CS (OR, 0.34; 95% CI, 0.20-0.57; P < .001) with moderate heterogeneity (I2 = 62%), and deep SWIs post CS (OR, 0.26; 95% CI, 0.11-0.65; P = .004) with moderate heterogeneity (I2 = 65%) compared with control as shown in Figures 2 and 3. However, there was no significant difference found between TV and control in superficial SWIs post CS (OR, 0.30; 95% CI, 0.07-1.30; P = .011) with moderate heterogeneity (I2 = 68%) as shown in Figure 4.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent review demonstrated the common reason for readmissions after 30 days of CABG were infection and sepsis (6.9–28.6%), cardiac arrhythmia (4.5–26.7%), congestive heart failure (5.8–15.7%), respiratory complications (1–20%) and pleural effusion (0.4–22.5%) [ 25 ]. A study done by Jadhao et al compared incidence of sternal wound SSIs among stapler and polyamide suture groups, and found higher incidence of SSIs in stapler group (9.72%) than the polyamide suture group (7.17%) [ 26 ]. In the present study, incidence of superficial SSI was recorded by 6 th week post-DOD in one subject of the Trulene® group.…”
Section: Discussionmentioning
confidence: 99%